FORMULASI SEDIAAN SABUN MANDI PADAT DARI EKSTRAK BUAH APEL (Malus domesticus) SEBAGAI SABUN KECANTIKAN KULIT - Adek Chan (Jurnal Ilmiah Manuntung, 2016)
As the development time of usage and utilization of traditional medicine in Indonesia is experiencing a very rapid progress. Interest of the community to utilize natural materials back to health is greatly improved. Apple or (pyrusmalus) is one among the faforit fruit in the family rosaceae or rose-mawaran. Apple plants allegedly came from around israel-Palestine, then spread throughout the world, including indonesia. Europe and Australia is the country’s most used to develop crop of apples in agribusiness. Apples contain a natural anti oxidant which is great for the health of the skin and eyes. This research uses research methods laboratory ekperimental Soap to be created with a penembahan extract of apples made with olive oil. Apple fruit is extracted by means of maceration using penyari ethanol. Ethanol extract of Apple made in the form of solid bath soaps and bath soaps performed the examination test includes solid Favorites, pH, testing methods and solid bath Soap Irritation Test made with a concentration of 2.5%, 3.5%, 4.5%. The results of the test checks gladness solid bath Soap preparations obtained are really like 13 people, like 4 people, 3 people and less like don’t like 0, pH 8.3-7.3, on the test of irritation in the preparations of solid bath SOAP from Apple fruit extracts do not cause skin redness and itching. The conclusion of the researchers extract of apples (Malusdomsticus) can be formulated in the form of preparation of solid bath Soap. The advice of researchers is expected for the next researcher to be able to formulate the Apple fruit extract (Malusdomesticus) in the form of other preparations, such as face masks.